Sentencing of Technical and Low-Level Supervision Violations: An Analysis of Fixed Effects Across Federal Judicial Districts - DaGrossa, Joseph A. (Criminal justice review, 2023)
A considerable amount of previous research has examined the iatrogenic effects of mass imprisonment. This work has often considered the fact that the sentencing of people for low-level supervision violations is a contributing factor to the prison population. Relatively little work, however, has examined the factors which specifically influence the sentencing of probation and parole violators for technical and other low-level infractions. The present study analyzed over 44,000 cases of individuals who appeared in federal courts between 2013 and 2017 for relatively minor violations of federal community-based supervision. Using multilevel analysis to account for the nested quality of federal sentencing data, the study examined assorted individual-level legal and extra-legal effects on various sentencing outcomes. Effects were found for gender, having admitted to supervision violations, and predicate offense of conviction. Implications are presented.